WRITTEN SPEECH ACTS FOUND IN ADVERTISEMENTS ON INDONESIAN ONLINE NEWS WEBSITES - Astriningsih, Nurhapsari; Setiawan, Widiarto Adhi; Bram, Barli (Universitas Negeri Makassar, 2020)
This study attempts to help senior high school English teachers in developing their teaching material about advertisement, which is included in the state mandated curriculum. Having analyzed 20 advertisements, we found two types of speech acts, namely representatives and directives.Â The representative acts used were 59% and directive acts were 41% of the data. The advertisement strategy in Indonesia utilized representative acts, which intended to highlight the good quality of the products or services, whereas, the use of directive acts was situational since it is usually preceded by the appearance of representative acts. Since both speech acts frequently appeared in the advertisements on Indonesian online news websites, we recommend that teachers should provide exposures toward the linguistic features, which support studentsâ€™ ability to produce advertisement texts containing representative and directive acts.